Water repellent flame retardant finishing agent based on polyphosphazene coated nanocellulose core-shell particles, and preparation and application thereof

CN122980217APending Publication Date: 2026-10-27ZHEJIANG SCI-TECH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611454609.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-18
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而含氟防水剂所含的全氟和多氟烷基化合物在自然环境中难以降解,具有极强的生物累积性和潜在毒性;卤素阻燃剂在燃烧时释放有毒和腐蚀性气体,二者均已被严格限制,因此,开发无氟、无卤、兼具拒水与阻燃双重功能且耐久性优异的环保型整理剂,是行业亟需突破的技术瓶颈

Benefits of technology

1.功能集成与协同增效:在单一纳米粒子上集成了阻燃与拒水功能。CNC内核提供膨胀型阻燃所需碳源,聚磷腈壳层提供酸源和气源,实现P-N协同阻燃;壳层表面通过稳定三氮唑环共价连接的疏水长链提供持久拒水效果,实现了拒水阻燃的一体化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122980217A_ABST
    Figure CN122980217A_ABST
Patent Text Reader

Abstract

The application provides a water-repellent flame-retardant finishing agent based on polyphosphazene coated nanocellulose core-shell particles and preparation and application thereof, which comprises core-shell nanoparticles, chitosan and an aqueous medium; wherein the core-shell nanoparticles take nanocellulose crystals modified by an amino silane coupling agent on the surface as the core, take polyphosphazene copolymerized with an azide group as the shell, and have end alkyne long-chain alkane covalently grafted on the polyphosphazene shell layer through an azide-alkyne cycloaddition reaction, and can have both water-repellent and flame-retardant double functions under the premise of being free of fluorine and halogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional finishing technology for textiles, and in particular to a water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles, its preparation and application. This water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles is fluorine-free and halogen-free, and has both water-repellent and flame-retardant functions. Background Technology

[0002] Water-repellent finishing of textiles is an indispensable basic function in fields such as outdoor clothing, protective workwear, and military equipment. Its core objective is to give fabrics the ability to prevent liquid water from wetting and penetrating, while preserving as much of the fabric's inherent breathability, softness, and wearing comfort as possible. In addition, flame-retardant finishing is equally important, as most applications require textiles to have both water-repellent and flame-retardant properties.

[0003] Currently, water-repellent finishing relies heavily on fluorocarbon compounds, while flame-retardant finishing primarily uses halogenated flame retardants and organophosphates. However, the perfluorinated and polyfluoroalkyl compounds contained in fluorinated waterproofing agents are difficult to degrade in the natural environment, exhibiting strong bioaccumulation and potential toxicity; halogenated flame retardants release toxic and corrosive gases during combustion, and both are strictly restricted. Therefore, developing fluorine-free, halogen-free, environmentally friendly finishing agents that combine water-repellent and flame-retardant functions with excellent durability is a technological bottleneck that the industry urgently needs to overcome. Summary of the Invention

[0004] The purpose of this invention is to provide a water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles, its preparation and application, which can have both water-repellent and flame-retardant functions without fluorine or halogen.

[0005] To achieve the above objectives, this technical solution provides a water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles, comprising: core-shell nanoparticles, chitosan, and an aqueous medium; wherein the core-shell nanoparticles have nanocellulose crystals modified with an aminosilane coupling agent as the core, and polyphosphazene copolymerized with azide groups as the shell, and terminal alkyne-based long-chain alkanes are covalently grafted onto the polyphosphazene shell through an azide-alkyne cycloaddition reaction.

[0006] Cellulose nanocrystals (CNCs) are derived from natural plant fibers and possess renewable, biodegradable, high specific surface area, and nano-effect properties. Their surface is rich in hydroxyl groups, serving as both reaction sites for chemical modification and as a carbon source framework for intumescent flame-retardant systems. Polyphosphazenes are hybrid polymers with alternating phosphorus-nitrogen double bonds as their main chain. Their main chain constitutes a PN-synergistic flame-retardant structure at the molecular level, with hexachlorocyclotriphosphazene (HCCP) being the most commonly used monomer in the synthesis of polyphosphazenes. This solution provides a water-repellent flame-retardant finishing agent based on polyphosphazene-coated cellulose nanoparticles. Polyphosphazene is covalently linked to the surface of cellulose nanoparticles in a shell form, creating a core-shell structure. The cellulose nanoparticle core provides the carbon source framework, while the polyphosphazene shell provides acid and gas sources, thus achieving flame-retardant functionality on a single nanoparticle. Furthermore, introducing hydrophobic long chains onto the shell surface simultaneously imparts water-repellent properties, providing a novel approach for multifunctional finishing of textiles.

[0007] The water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles uses nanocellulose crystals with surfaces modified by aminosilane coupling agents as the core. This core serves as a rigid template and biomass carrier for the inorganic / organic hybrid core-shell structure, which can endow the finishing agent with good biocompatibility and affinity for cellulose fabrics. The amino groups of the aminosilane coupling agent on the surface of the nanocellulose crystals provide anchoring points for the subsequent copolymerization growth of the polyphosphazene shell.

[0008] In some embodiments, the aminosilane coupling agent is 3-aminopropyltriethoxysilane, which can construct a high-density, highly active covalent amino graft layer on the surface of CNCs. This ensures the continuity and strength of the in-situ copolymerization growth of the polyphosphazene shell, and effectively avoids the agglomeration and dispersibility deterioration of nanoparticles caused by excessive self-polymerization of the silane coupling agent. This lays a solid interfacial foundation for the subsequent preparation of a core-shell water-repellent and flame-retardant finishing agent with high durability and high dispersibility.

[0009] In some embodiments, the mass ratio of core-shell nanoparticles to chitosan is 1:0.1 to 1:0.2.

[0010] The core-shell nanoparticles use polyphosphazene copolymerized with azide groups as the shell. This shell, as the polyphosphazene skeleton, can contain a large amount of phosphorus (P) and nitrogen (N) elements. When heated, it can promote char formation and release non-combustible gases, giving the finishing agent excellent gas-solid synergistic flame retardant properties.

[0011] In some embodiments, polyphosphazenes with azide groups are copolymerized from hexachlorocyclotriphosphazenes and azide-based pentachlorocyclotriphosphazenes. This process can impart efficient phosphorus-nitrogen synergistic flame retardant properties to core-shell nanoparticles while precisely introducing highly active azide groups into the shell layer. This not only avoids the hydrolysis risks caused by direct nucleophilic substitution of traditional P-Cl bonds, but also provides key technical support for the subsequent construction of highly durable water-repellent flame retardant finishing agents through efficient and mild click chemistry (CuAAC) directional grafting of long-chain alkanes.

[0012] Furthermore, the molar ratio of hexachlorocyclotriphosphazene to azide-pentachlorocyclotriphosphazene is 6:1 to 10:1.

[0013] The surface of the core-shell nanoparticles is covalently grafted with terminal alkyne-based long-chain alkanes onto the polyphosphazene shell via an azide-alkyne cycloaddition reaction. That is, the terminal alkyne-based long-chain alkanes are connected to the polyphosphazene shell through 1,2,3-triazole heterocycles.

[0014] In some embodiments, the terminal alkyne-based long-chain alkane is 1-octadecylene, which can drive the azide group to be completely converted into a highly stable 1,2,3-triazole structure while overcoming the steric hindrance of the nanoparticle interface reaction. This enables high-density and high-fastness directional grafting of hydrophobic long chains onto the particle surface. At the same time, it avoids washing problems and dispersibility deterioration caused by excessive hydrophobic long chain residue, ensuring the finishing agent's excellent and durable water-repellent effect.

[0015] Furthermore, the molar ratio of the azide group to 1-octadecylene is 1:1 to 1:3.

[0016] In one specific embodiment, the core-shell nanoparticles are CNC@PDCP-C18, with a core of nanocellulose crystals and a shell of octadecyl functionalized polyphosphazene containing triazole linkers, as shown in the following structure. Figure 1 As shown.

[0017] The chitosan in this solution contains a large number of primary amino and hydroxyl groups. In a weakly acidic aqueous solution, it is protonated and carries a positive charge. On the one hand, it can form a physical / chemical cross-linking network with negatively charged or multifunctional core-shell particles. On the other hand, it can form hydrogen bonds and electrostatic attraction with the surface of textile fibers (such as cotton, polyester, etc.), which significantly improves the adhesion of the finishing agent during the washing and brushing process of the fabric and maintains a good fabric hand feel.

[0018] In some embodiments, the mass ratio of core-shell nanoparticles to chitosan is 1:0.1 to 1:0.2.

[0019] The aqueous medium in this solution is deionized water, which is used to suspend core-shell particles and dissolve chitosan, providing an environmentally friendly and non-toxic dispersion system.

[0020] In some embodiments, the solid content of the core-shell nanoparticles in the aqueous medium is 5% to 15%.

[0021] Secondly, this solution provides a method for preparing a water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles, comprising the following steps: (1) Disperse nanocellulose crystals in anhydrous N,N-dimethylformamide, add aminosilane coupling agent, react for a period of time under nitrogen protection and heating, and then wash and dry to obtain surface-aminated nanocellulose crystals. (2) The surface-aminated nanocellulose crystals were dispersed in anhydrous tetrahydrofuran, and hexachlorocyclotriphosphazene and azide-based pentachlorocyclotriphosphazene were added. The reaction was carried out under the conditions of acid binding agent and heating. After washing and drying, core-shell nanoparticles with embedded azide groups were obtained. (3) Disperse the core-shell nanoparticles with embedded azide groups in anhydrous N,N-dimethylformamide, add terminal alkyne long-chain alkanes, and carry out azide-alkyne cycloaddition click chemical reaction in the presence of copper catalyst and ligand. After the reaction, remove copper ions, wash and dry to obtain hydrophobic functionalized core-shell nanoparticles. (4) Disperse hydrophobic functionalized core-shell nanoparticles in an aqueous medium to prepare an aqueous dispersion; dissolve chitosan in an aqueous acetic acid solution to prepare a chitosan solution; add the chitosan solution to the aqueous dispersion under stirring conditions and mix well to obtain a water-repellent flame retardant finishing agent.

[0022] In step (1), the aminosilane coupling agent is selected as 3-aminopropyltriethoxysilane.

[0023] In step (1), the mass ratio of nanocellulose crystals to aminosilane coupling agent is 1:2, the reaction temperature is 70~90℃, and the reaction time is 6~12 hours.

[0024] In step (2), the molar ratio of hexachlorocyclotriphosphazene to azide-based pentachlorocyclotriphosphazene is 6:1 to 10:1, and the mass ratio of surface-aminated nanocellulose crystals to total phosphazene monomers is controlled at 1:1 to 1:3.

[0025] In step (2), the acid-binding agent is anhydrous triethylamine.

[0026] In step (2), the heating conditions are a reaction temperature of 50~70℃ and a reaction time of 3~6 hours.

[0027] In step (3), the terminal alkyne long-chain alkane is 1-octadecyne.

[0028] In step (3), the molar ratio of azide group to 1-octadecylene is 1:1 to 1:3.

[0029] In step (3), the copper catalyst is cuprous bromide and the ligand is pentamethyldiethylenetriamine.

[0030] In step (3), the reaction temperature of the azide-alkyne cycloaddition click chemistry reaction is 40~50℃ and the reaction time is 8~16 hours.

[0031] In step (4), the aqueous medium is deionized water.

[0032] In step (4), the solid content of the hydrophobic functionalized core-shell nanoparticles in the dispersion is 8-12%, the concentration of the chitosan solution is 1-3%, and the solvent is 0.5-2% aqueous acetic acid solution.

[0033] In step (4), the mass ratio of hydrophobic functionalized core-shell nanoparticles to chitosan is 1:0.1 to 1:0.5.

[0034] Thirdly, this solution provides an application method for a water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles, which is applied to form a water-repellent and flame-retardant finishing layer on the surface of fabrics.

[0035] In some embodiments, the fabric is immersed in a water-repellent and flame-retardant finishing agent, and after being dried and baked, a durable fluorine-free water-repellent and flame-retardant finished fabric is obtained by padding and drying.

[0036] Specifically, the fabric is immersed in the water-repellent and flame-retardant finishing agent, and then subjected to a one-dip-one-pick treatment with a pick-up rate of 60% to 80%. Subsequently, it is dried at 60°C to 90°C and then baked at 130°C to 170°C for 3 to 10 minutes to form a water-repellent and flame-retardant finishing layer on the fabric surface.

[0037] Compared with existing technologies, this technical solution has the following characteristics and beneficial effects: 1. Functional Integration and Synergistic Effect: Flame retardant and water-repellent functions are integrated on a single nanoparticle. The CNC core provides the carbon source required for intumescent flame retardancy, while the polyphosphazene shell provides the acid and gas sources, achieving PN synergistic flame retardancy; the shell surface provides a durable water-repellent effect through long hydrophobic chains covalently linked by stable triazole rings, realizing the integration of water repellency and flame retardancy.

[0038] 2. Controllable preparation of shell structure: Uniform amino initiation sites are first anchored on the CNC surface, and then the phosphazene monomer is initiated into confined polymerization. The shell grows directionally from the CNC surface outward, avoiding self-nucleation in solution. The shell thickness can be precisely controlled by adjusting the monomer feed ratio. The structure is stable and repeatable between batches, solving the problems of random shell formation and uncontrollable shell thickness in traditional methods.

[0039] 3. Durability and controllability of hydrophobic function: By using the azide group embedded in the shell as a fixed-point and quantitative handle, hydrophobic long chains are grafted through click chemical reaction, avoiding the defects of uncertain grafting density caused by hydrolysis or alcoholysis in the traditional P-Cl bond route, which greatly improves the durability and batch consistency of the water-repellent function.

[0040] 4. Environmental friendliness and wearing comfort: The entire system is fluorine-free and halogen-free, and the main materials contain natural polymers, which are green and environmentally friendly; the polyphosphazene shell is only at the nanoscale, and the coating is thin and smooth after finishing, which has little impact on the fabric's feel, breathability and moisture permeability, and maintains good wearing comfort. Attached Figure Description

[0041] Figure 1 This is a schematic diagram of the structure of the CNC@PDCP-C18 core-shell nanoparticles in this scheme.

[0042] Figure 2 This is a SEM image of the CNC@PDCP-C18 core-shell nanoparticles obtained in Example 1.

[0043] Figure 3 This is the XPS characterization image of the CNC@PDCP-C18 core-shell nanoparticles obtained in Example 1. Detailed Implementation

[0044] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0045] For those skilled in the art, any modifications, equivalent substitutions, or improvements made to the technical solutions of this invention without departing from the spirit and essence of this invention should be included within the scope of protection of this invention.

[0046] Raw materials and instruments: Unless otherwise specified, all raw materials, reagents and catalysts used in the embodiments and comparative examples of this invention can be purchased commercially or prepared according to methods known in the art; the instruments and equipment used are all conventional laboratory or industrial production equipment in the art.

[0047] Example 1 Preparation method of water-repellent and flame-retardant finishing agent: (1) 1 g of nanocellulose crystals (CNC) was added to 80 mL of anhydrous N,N-dimethylformamide (DMF) and ultrasonically dispersed for 30 min to obtain a uniform CNC dispersion. 2.0 g of 3-aminopropyltriethoxysilane (APTES) was added dropwise to the dispersion, and the mixture was heated to 80 °C under nitrogen protection and stirred for 8 h. After cooling, the mixture was centrifuged, washed three times alternately with DMF and ethanol, and dried under vacuum at 60 °C to obtain CNC-NH2.

[0048] (2) 0.8 g CNC-NH2 was ultrasonically dispersed in 100 mL of anhydrous tetrahydrofuran, and 1.39 g hexachlorocyclotriphosphazene (HCCP) and 0.178 g azide-pentachlorocyclotriphosphazene (N3P3Cl5) (molar ratio 8:1) were added. 3 mL of anhydrous triethylamine was added dropwise. The mixture was heated to 60 °C and reacted for 4 h under ultrasonic assistance and a nitrogen atmosphere. After cooling, the mixture was centrifuged and washed with anhydrous tetrahydrofuran and deionized water until the supernatant was free of chloride ions. The supernatant was then dried under vacuum at 60 °C to obtain CNC@PDCP-N3.

[0049] (3) 0.6 g of CNC@PDCP-N3 was ultrasonically dispersed in 50 mL of anhydrous DMF, and 0.54 g of 1-octadecylene was added. Under nitrogen atmosphere, 0.05 mmol of cuprous bromide (CuBr) and 0.05 mmol of pentamethyldiethylenetriamine (PMDETA) were added sequentially, and the reaction was carried out at 45 °C for 12 h. After the reaction was completed, excess EDTA-2Na aqueous solution was added, and the mixture was stirred at 50 °C for 2 h to remove copper. After centrifugation, the mixture was washed with deionized water and ethanol, and dried under vacuum at 60 °C to obtain CNC@PDCP-C18.

[0050] (4) CNC@PDCP-C18 was ultrasonically dispersed in deionized water to prepare a dispersion with a solid content of 10%; chitosan was dissolved in 1% acetic acid aqueous solution to prepare a chitosan solution with a concentration of 3%. 25g of chitosan solution was slowly added to 50g of CNC@PDCP-C18 dispersion under stirring, and stirring was continued at 40℃ for 1h to obtain a water-repellent and flame-retardant finishing agent.

[0051] Finishing methods for water-repellent and flame-retardant fabrics: The fabric is immersed in the above finishing agent, dipped and rubbed once, with a pick-up rate of 80%, dried at 80°C, and baked at 130°C for 5 minutes to obtain a durable, fluorine-free, water-repellent, and flame-retardant finished fabric.

[0052] X-ray photoelectron spectroscopy (XPS) was performed on the CNC@PDCP-C18 prepared in step (3) of Example 1. The results are as follows: Figure 3 As shown, where: Figure 3 Figure (a) in the image is the full spectrum; Figure 3 Figure (b) in the figure is the C1sXPS fitted spectrum; Figure 3 Figure (c) in the figure is the N1s XPS fitting spectrum; Figure 3 Figure (d) in the figure is the P2p XPS fitting spectrum.

[0053] Depend on Figure 3 As can be seen in (a), the sample surface mainly contains elements such as C, O, N, P, and Si; Figure 3 As shown in (b), the C1s spectrum has a strong main peak at 284.8 eV attributed to CC, and a peak at approximately 286.2 eV attributed to CO / CN; Figure 3 In the (c)N1s spectrum, approximately 398.5 eV is attributed to P=N in the polyphosphazene skeleton; approximately 399.8 eV is attributed to CN / NN, including the triazole ring and the amino group in the aminosilane coupling agent; approximately 400.9 eV is attributed to NN=N in the triazole ring; no obvious azide group characteristic peaks were observed at 404-405 eV, indicating that the azide-acetylene click reaction has converted the azide group into 1,2,3-triazole; Figure 3 In the (d)P2p spectrum, P2p is shown at 133-134 eV. 3 / 2 and P 2p 1 / 2 The two peaks, with an area ratio of approximately 2:1, are attributed to the P=N / PN structure within the polyphosphazene shell. These results indicate that the CNC@PDCP-C18 prepared in Example 1 possesses a polyphosphazene shell and an octadecyl long-chain structure grafted onto the shell surface.

[0054] Example 2 Preparation method of water-repellent and flame-retardant finishing agent: (1) 1 g of nanocellulose crystals (CNC) was added to 80 mL of anhydrous N,N-dimethylformamide (DMF) and ultrasonically dispersed for 30 min to obtain a uniform CNC dispersion. 2.0 g of 3-aminopropyltriethoxysilane (APTES) was added dropwise to the dispersion, and the mixture was heated to 80 °C under nitrogen protection and stirred for 8 h. After cooling, the mixture was centrifuged, washed three times alternately with DMF and ethanol, and dried under vacuum at 60 °C to obtain CNC-NH2.

[0055] (2) 0.8 g CNC-NH2 was ultrasonically dispersed in 100 mL of anhydrous tetrahydrofuran, and 1.39 g hexachlorocyclotriphosphazene (HCCP) and 0.236 g azide-pentachlorocyclotriphosphazene (N3P3Cl5) (molar ratio 6:1) were added. 3 mL of anhydrous triethylamine was added dropwise. The mixture was heated to 60 °C and reacted for 4 h under ultrasonic assistance and a nitrogen atmosphere. After cooling, the mixture was centrifuged and washed with anhydrous tetrahydrofuran and deionized water until the supernatant was free of chloride ions. The supernatant was then dried under vacuum at 60 °C to obtain CNC@PDCP-N3.

[0056] (3) 0.6 g of CNC@PDCP-N3 was ultrasonically dispersed in 50 mL of anhydrous DMF, and 0.54 g of 1-octadecylene was added. Under nitrogen atmosphere, 0.05 mmol of cuprous bromide (CuBr) and 0.05 mmol of pentamethyldiethylenetriamine (PMDETA) were added sequentially, and the reaction was carried out at 45 °C for 12 h. After the reaction was completed, excess EDTA-2Na aqueous solution was added, and the mixture was stirred at 50 °C for 2 h to remove copper. After centrifugation, the mixture was washed with deionized water and ethanol, and dried under vacuum at 60 °C to obtain CNC@PDCP-C18.

[0057] (4) CNC@PDCP-C18 was ultrasonically dispersed in deionized water to prepare a dispersion with a solid content of 8%; chitosan was dissolved in 1% acetic acid aqueous solution to prepare a chitosan solution with a concentration of 3%. 25g of chitosan solution was slowly added to 50g of CNC@PDCP-C18 dispersion under stirring, and stirring was continued at 40℃ for 1h to obtain a water-repellent and flame-retardant finishing agent.

[0058] Finishing methods for water-repellent and flame-retardant fabrics: The fabric is immersed in the above finishing agent, dipped and rubbed once, with a pick-up rate of 80%, dried at 80°C, and baked at 130°C for 5 minutes to obtain a durable, fluorine-free, water-repellent, and flame-retardant finished fabric.

[0059] Example 3 Preparation method of water-repellent and flame-retardant finishing agent: (1) 1 g of nanocellulose crystals (CNC) was added to 80 mL of anhydrous N,N-dimethylformamide (DMF) and ultrasonically dispersed for 30 min to obtain a uniform CNC dispersion. 2.0 g of 3-aminopropyltriethoxysilane (APTES) was added dropwise to the dispersion, and the mixture was heated to 80 °C under nitrogen protection and stirred for 8 h. After cooling, the mixture was centrifuged, washed three times alternately with DMF and ethanol, and dried under vacuum at 60 °C to obtain CNC-NH2.

[0060] (2) 0.8 g CNC-NH2 was ultrasonically dispersed in 100 mL of anhydrous tetrahydrofuran, and 1.39 g of hexachlorocyclotriphosphazene (HCCP) and 0.142 g of azide-pentachlorocyclotriphosphazene (N3P3Cl5) (molar ratio 10:1) were added. 3 mL of anhydrous triethylamine was added dropwise. The mixture was ultrasonically assisted and heated to 50 °C under a nitrogen atmosphere for 6 h. After cooling, the mixture was centrifuged and washed with anhydrous tetrahydrofuran and deionized water until the supernatant was free of chloride ions. The supernatant was then dried under vacuum at 60 °C to obtain CNC@PDCP-N3.

[0061] (3) 0.6 g of CNC@PDCP-N3 was ultrasonically dispersed in 50 mL of anhydrous DMF, and 0.54 g of 1-octadecylene was added. Under nitrogen atmosphere, 0.05 mmol of cuprous bromide (CuBr) and 0.05 mmol of pentamethyldiethylenetriamine (PMDETA) were added sequentially, and the reaction was carried out at 45 °C for 12 h. After the reaction was completed, excess EDTA-2Na aqueous solution was added, and the mixture was stirred at 50 °C for 2 h to remove copper. After centrifugation, the mixture was washed with deionized water and ethanol, and dried under vacuum at 60 °C to obtain CNC@PDCP-C18.

[0062] (4) CNC@PDCP-C18 was ultrasonically dispersed in deionized water to prepare a dispersion with a solid content of 12%; chitosan was dissolved in 1% acetic acid aqueous solution to prepare a chitosan solution with a concentration of 3%. 25g of chitosan solution was slowly added to 50g of CNC@PDCP-C18 dispersion under stirring, and stirring was continued at 40℃ for 1h to obtain a water-repellent and flame-retardant finishing agent.

[0063] Finishing methods for water-repellent and flame-retardant fabrics: The fabric is immersed in the above finishing agent, dipped and rubbed once, with a pick-up rate of 80%, dried at 80°C, and baked at 130°C for 5 minutes to obtain a durable, fluorine-free, water-repellent, and flame-retardant finished fabric.

[0064] Example 4 Preparation method of water-repellent and flame-retardant finishing agent: (1) 1 g of nanocellulose crystals (CNC) was added to 80 mL of anhydrous N,N-dimethylformamide (DMF) and ultrasonically dispersed for 30 min to obtain a uniform CNC dispersion. 2.0 g of 3-aminopropyltriethoxysilane (APTES) was added dropwise to the dispersion, and the mixture was heated to 80 °C under nitrogen protection and stirred for 8 h. After cooling, the mixture was centrifuged, washed three times alternately with DMF and ethanol, and dried under vacuum at 60 °C to obtain CNC-NH2.

[0065] (2) 0.8 g CNC-NH2 was ultrasonically dispersed in 100 mL of anhydrous tetrahydrofuran, and 1.39 g hexachlorocyclotriphosphazene (HCCP) and 0.178 g azide-pentachlorocyclotriphosphazene (N3P3Cl5) (molar ratio 8:1) were added. 3 mL of anhydrous triethylamine was added dropwise. The mixture was heated to 60 °C and reacted for 4 h under ultrasonic assistance and a nitrogen atmosphere. After cooling, the mixture was centrifuged and washed with anhydrous tetrahydrofuran and deionized water until the supernatant was free of chloride ions. The supernatant was then dried under vacuum at 60 °C to obtain CNC@PDCP-N3.

[0066] (3) 0.6 g of CNC@PDCP-N3 was ultrasonically dispersed in 50 mL of anhydrous DMF, and 0.54 g of 1-octadecylene was added. Under nitrogen atmosphere, 0.05 mmol of cuprous bromide (CuBr) and 0.05 mmol of pentamethyldiethylenetriamine (PMDETA) were added sequentially, and the reaction was carried out at 50 °C for 10 h. After the reaction was completed, excess EDTA-2Na aqueous solution was added, and the mixture was stirred at 50 °C for 2 h to remove copper. After centrifugation, the mixture was washed with deionized water and ethanol, and dried under vacuum at 60 °C to obtain CNC@PDCP-C18.

[0067] (4) CNC@PDCP-C18 was ultrasonically dispersed in deionized water to prepare a dispersion with a solid content of 10%; chitosan was dissolved in 1% acetic acid aqueous solution to prepare a chitosan solution with a concentration of 3%. 25g of chitosan solution was slowly added to 50g of CNC@PDCP-C18 dispersion under stirring, and stirring was continued at 40℃ for 1h to obtain a water-repellent and flame-retardant finishing agent.

[0068] Finishing methods for water-repellent and flame-retardant fabrics: The fabric is immersed in the above finishing agent, dipped and rubbed once, with a pick-up rate of 80%, dried at 80°C, and baked at 150°C for 3 minutes to obtain a durable, fluorine-free, water-repellent, and flame-retardant finished fabric.

[0069] [Actual Performance Data]

[0070] Those skilled in the art should understand that the technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments have been described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0071] The above embodiments are merely illustrative of several implementation methods of this application, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of this application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims.

Claims

1. A water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles, characterized in that, include: The composition consists of core-shell nanoparticles, chitosan, and an aqueous medium. The core-shell nanoparticles use nanocellulose crystals modified with an aminosilane coupling agent as the core and polyphosphazene copolymerized with azide groups as the shell. Terminal alkyne long-chain alkanes are covalently grafted onto the polyphosphazene shell through an azide-alkyne cycloaddition reaction. The aminosilane coupling agent is 3-aminopropyltriethoxysilane.

2. The water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles according to claim 1, characterized in that, The mass ratio of core-shell nanoparticles to chitosan is 1:0.1 to 1:0.2, and the solid content of core-shell nanoparticles in aqueous medium is 8% to 12%.

3. The water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles according to claim 1, characterized in that, The mass ratio of nanocellulose crystals to aminosilane coupling agent is 1:2, and the molar ratio of azide group to 1-octadecylene is 1:1 to 1:

3.

4. The water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles according to claim 1, characterized in that, Terminal alkyne-based long-chain alkanes are linked to the polyphosphazene shell via a 1,2,3-triazole heterocycle.

5. The water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles according to claim 1, characterized in that, Polyphosphazenes with azide groups are copolymerized from hexachlorocyclotriphosphazenes and azide-pentachlorocyclotriphosphazenes, with a molar ratio of hexachlorocyclotriphosphazenes to azide-pentachlorocyclotriphosphazenes of 6:1 to 10:

1.

6. A method for preparing a water-repellent and flame-retardant finishing agent based on polyphosphazene-coated nanocellulose core-shell particles according to any one of claims 1 to 5, comprising the following steps: (1) Disperse nanocellulose crystals in anhydrous N,N-dimethylformamide, add aminosilane coupling agent, react for a period of time under nitrogen protection and heating, and then wash and dry to obtain surface-aminated nanocellulose crystals. (2) The surface-aminated nanocellulose crystals were dispersed in anhydrous tetrahydrofuran, and hexachlorocyclotriphosphazene and azide-based pentachlorocyclotriphosphazene were added. The reaction was carried out under the conditions of acid binding agent and heating. After washing and drying, core-shell nanoparticles with embedded azide groups were obtained. (3) Disperse the core-shell nanoparticles with embedded azide groups in anhydrous N,N-dimethylformamide, add terminal alkyne long-chain alkanes, and carry out azide-alkyne cycloaddition click chemical reaction in the presence of copper catalyst and ligand. After the reaction, remove copper ions, wash and dry to obtain hydrophobic functionalized core-shell nanoparticles. (4) Disperse hydrophobic functionalized core-shell nanoparticles in an aqueous medium to prepare an aqueous dispersion; dissolve chitosan in an aqueous acetic acid solution to prepare a chitosan solution; add the chitosan solution to the aqueous dispersion under stirring conditions and mix well to obtain a water-repellent flame retardant finishing agent.

7. The preparation method according to claim 6, characterized in that, In step (1), the aminosilane coupling agent is 3-aminopropyltriethoxysilane.

8. The preparation method according to claim 6, characterized in that, In step (3), the terminal alkyne long-chain alkane is 1-octadecyne.

9. The preparation method according to claim 6, characterized in that... The mass ratio of nanocellulose crystals to 3-aminopropyltriethoxysilane is 1:2, the molar ratio of hexachlorocyclotriphosphazene to azide-pentachlorocyclotriphosphazene is 6:1 to 10:1, and the mass ratio of surface-aminated nanocellulose crystals to total phosphazene monomers is controlled at 1:1.8 to 1:2.

2.

10. A method for finishing fabrics using the water-repellent and flame-retardant finishing agent as described in any one of claims 1-5, characterized in that, Includes the following steps: The fabric is immersed in a water-repellent and flame-retardant finishing agent, and then dried and baked to obtain a durable, fluorine-free water-repellent and flame-retardant finished fabric.